2022
DOI: 10.3390/ijms232112830
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Virulent and Non-Productive Phages Synergizes the Immune System against Salmonella Typhimurium Systemic Infection

Abstract: Effective phage cocktails consisting of multiple virus types are essential for successful phage therapy against pandrug-resistant pathogens, including Salmonella enterica serovar (S.) Typhimurium. Here we show that a Salmonella phage, F118P13, with non-productive infection and a lytic phage, PLL1, combined to inhibit pandrug-resistant S. Typhimurium growth and significantly limited resistance to phages in vitro. Further, intraperitoneal injection with this unique phage combination completely protected mice fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…By further testing the load of Salmonella in various organs of infected chicks, we found that phage treatment greatly reduced the bacterial load in various organs, and the decrease of the number of Salmonella in the spleen and bursa was significantly greater than that in the liver and cecal contents, which may be due to higher phage titers in immune organs ( Figure 1F ). The result that phages tend to reside in immune organs was also observed previously in a mouse model treated with this phage combination, in which the titer and residence time of phage in spleen and thymus of mice were significantly higher than those in liver and kidney ( Liang et al, 2022 ). The time of bacteriophage persistence and their concentration in a particular organ strongly depends on the absence or presence of susceptible bacteria in an animal's body ( Dabrowska et al, 2005 ).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…By further testing the load of Salmonella in various organs of infected chicks, we found that phage treatment greatly reduced the bacterial load in various organs, and the decrease of the number of Salmonella in the spleen and bursa was significantly greater than that in the liver and cecal contents, which may be due to higher phage titers in immune organs ( Figure 1F ). The result that phages tend to reside in immune organs was also observed previously in a mouse model treated with this phage combination, in which the titer and residence time of phage in spleen and thymus of mice were significantly higher than those in liver and kidney ( Liang et al, 2022 ). The time of bacteriophage persistence and their concentration in a particular organ strongly depends on the absence or presence of susceptible bacteria in an animal's body ( Dabrowska et al, 2005 ).…”
Section: Resultssupporting
confidence: 83%
“…We previously demonstrated that a combination containing virulent and nonproductive phages could not only inhibit pandrug-resistant S . Typhimurium growth and the emergence of phage resistance in vitro, but also protected mice from Salmonella -induced death with the help of immune system ( Liang et al, 2022 ) . In the current study, we further explored the effect of this phage combination in a SPF chick model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations